Responses of diversity and carbon and nitrogen cycling genes of soil microorganisms to pomegranate (Punica granatum L.)/faba bean (Vicia faba L.) intercropping - Zhang, Degang; Zhu, Dirui; Wang, Miao; Shi, Xian; Chen, Yongchuan (Frontiers in Forests and Global Change, 2023)
The negative impacts of continuous cropping and long-term single crop planting on soil quality significantly restrict the high yield cultivation of perennial orchards. Intercropping can facilitate continuous cropping and improve the quality of the soil environment. However, it is still unclear whether the interplanting of faba bean in perennial orchards will increase the concentration of soil nutrients, change the composition of the soil microbial community, and increase the abundance of carbon (C) and nitrogen (N) cycling microorganisms. We interplanted faba beans in a perennial pomegranate orchard, and used sequencing and qPCR technology to study the effects on soil microbial diversity and C and N cycling genes. The results indicated that the interplanting of faba bean significantly increased the total N concentration by 28.6%, total phosphorus(P) concentration by 73.0% and available P concentration by 103.4%. The composition and structure of the soil microbial community were significantly changed, and the bacteria significantly enriched were Gaiellales and Rhizobiales at the order level and Nitrosomonadaceae at the family level. The fungi significantly enriched were Pezizomycetes at the class level, Pezizales and Sordariales at the order level, Ascodesmidaceae and Ophiocordycipitaceae at the family level, Cephaliophora, Parachaetomium, and Purpureocillium at the genus level, and Lilacinum, Lavendulum, Carinthiacum, Tropica, Chaetomium, and Delphinoides at the species level. The copy numbers of cbbL and nifH genes in soil were significantly increased by 79.9 and 168.5%, respectively. Changes in major nutrient elements explained 71.2% of the variance at the family level for bacteria and 46.0% of the variance at the family level for fungi. These results provided a scientific basis for the improvement of soil environmental quality and soil microorganisms by interplanting cash crops in perennial orchards.